Thermal degradation of aluminum formate sol-gel; synthesis of α-alumina and characterization by 1H, 13C and 27Al MAS NMR and XRD spectroscopy - José H. Roque-Ruiz (Results in Physics, 2016)
Thermal transformation of aluminum formate sol-gel to α-Al2O3 is reported. XRD and IR spectroscopy confirmed the presence of the precursor at 25 °C, and showed the precursor hydroxide at 200 °C. After calcinations, amorphous Al2O3 and η-Al2O3 were present at 400 °C and 800 °C, respectively. Coordination numbers and chemical interactions were determined b6y MAS nuclear magnetic resonance on different elements. 27Al MAS NMR study showed that sol-gels contain 6-coordinated aluminum ions. Four, five and six-coordinated aluminum species were present after calcinations at 400 °C. The transformation into α-Al2O3 was observed at 1050 °C. 1H MAS NMR was used to characterize aging conditions. According to TGA and DSC, total weight loss of 91.4% was due to dehydration and decarboxylation. Thermal decomposition and transition processes were represented by five endothermic peaks and one exothermic peak for the formation η-alumina, and finally, an endothermic peak for α-alumina formation. SEM images of sintered materials revealed a porous microstructure with intertwined microwires. This methodology produced a mesoporous α-Al2O3 with surface area of 5.48 m2/g and pore diameter around 3.37 nm. Keywords: Aluminum formate, Sol-gel, α-Alumina, NMR spectroscopy